Grit As Predictor Of Psychological Capital, Flourishing, Self-Reliance And Life Satisfaction Among University Students: The Role Of Resilience As Mediator - Ostovar, Shahla (2024)
This study examines the association between grit, defined as the combination of perseverance of effort and consistency of interest for long-term goals, and various dimensions of well-being, including resilience, psychological capital, flourishing, self-reliance, and life satisfaction among university students. The investigation adopts self-determination theory framework, which emphasizes on individuals' beliefs about their abilities and motivation to achieve goals. Grit is aligned with growth motivation as proposed by the mindset theory. Participants were 447 university students enrolled at a Malaysian public university. Three hundred and thirty-three (75.3%) were females, while 120 (26.4%) were males. The majority of the participants were between 22 to 25 years old (317; 69.9%), followed by 18 to 21 years (127; 28.1%). Instruments employed in this study include Grit scale, Connor-Davidson Resilience scale, PsyCap Questionnaire (PCQ-12), Flourishing scale, Self-reliance scale (SRS), and Life Satisfaction scale. Confirmatory factor analyses and omega (ω) reliability coefficients were employed to assess the reliability and validity of all scales used in the study. The results indicated that the scales consistently and accurately measured the intended constructs. The study was investigated both direct and indirect (mediating) effects of grit and dimensions of well-being. The findings of this study confirmed that grit was significant predictor of psychological capital, flourishing, self-reliance, and life satisfaction.